Effect of Gd3+, Bi3+, or Sm3+ on luminescent properties of La2−xMgTiO6:xEu3+ phosphors. (25th October 2018) - Xie, Huidong; Su, Binbin; Tan, Yurong; Zhao, Yajuan; Chai, Shouning
Abstract: Single phase of Bi 3+, Gd 3+, Sm 3+ and Eu 3+ co‐doped La2 MgTiO6 red phosphors were synthesized by high temperature solid‐state method. The phase composition, morphology and fluorescent properties of the phosphors were analyzed by X‐ray diffraction (XRD), scanning electron microscopy (SEM) and fluorescence spectrometer. The La2‐ x MgTiO6 : x Eu 3+ phosphors can be excited by UV (396 nm) and blue (465 nm) light‐emitting diode (LED) chips and show a strong red emitting with dominated wavelength at 615 nm. The optimum doping concentration of Eu 3+ ion for La2 MgTiO6 is x  = 0.5. The luminescent intensities of 5 D0  →  7 F2 transition of Eu 3+ in La1.5‐ y MgTiO6 :0.5Eu 3+, y Bi 3+ /Gd 3+ /Sm 3+ were 1.31 times, 1.32 times and 1.88 times that of La1.5 MgTiO6 :0.5Eu 3+ at y  = 0.08, 0.06, 0.06 for Bi 3+, Gd 3+, or Sm 3+ sensitizer, respectively. The chromaticity coordinates of La1.44 MgTiO6 :0.5Eu 3+, 0.06Sm 3+, (0.6342, 0.3513) were very close to those of the National Television Standard Committee (NTSC) standard red light coordinates.